Analisis Jumlah Bakteri Pasta Gigi Cangkang Anadara granosa yang Diberi Citrus medica Dengan Waktu Penyimpanan Yang Berbeda: Analisis Jumlah Bakteri Pasta Gigi Cangkang Anadara granosa yang Diberi Citrus medica Dengan Waktu Penyimpanan Yang Berbeda - Solang, Margaretha; Hasan, Marwan; Kumaji, Syam S. (Universitas Jambi, 2021)
The objective of the present work was aimed at analyzing the number of bacteria in Anadara granosa shell Toothpaste with the addition of Citrus medica with different storage duration. Relying on a completely randomized design, the factors of this research consisted of two, namely v me of the extract of Citrus medica with different treatments (0 mL, 2 mL, 4 mL, and 6 mL) and the storage duration with different treatments (1 day, 7 days, 14 days, 21 days, and 28 days) with six replications.Â A total plate count (TPC) method was applied in calculating of bacteria. The data were analyzed using a two-way ANOVA and a DMRT test with a significance of 5%. The results found that the provision of Citrus medica with different storage times interacted significantly (p = 0.00) on the number bacteria in Anadara granosa shell Toothpaste. The Number of bacteria of Anadara granosa toothpaste with the addition of 6 mL of Citrus medica stored for 28 days was 9.0 x 101; this was within the normal limit set by the Indonesian National Standard (SNI).